2021
DOI: 10.1177/25148486211060657
|View full text |Cite
|
Sign up to set email alerts
|

(Counter)mapping renewables: Space, justice, and politics of wind and solar power in Mexico

Abstract: The ongoing expansion of renewable energies entails major spatial reconfigurations with social, environmental, and political dimensions. These emerging geographies are, however, in the process of taking shape, as their early configurations are still open to democratic intervention and contestation. While a recent line of research highlights the prominent role that maps are playing in directing such processes, the potential effects of countermapping on these evolving geographies have not yet been explored. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…This is especially so when accounting for associated factors like trade, with China the global manufacturing hub for solar PV modules. Space and the ways in which territories are opened up for solar development can promote socio-technical transformation, but equally reproduce business-as-usual geographical and geopolitical power constellations (Avila et al 2022).…”
Section: Review and Methodology: Towards Identifying Principles Of So...mentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially so when accounting for associated factors like trade, with China the global manufacturing hub for solar PV modules. Space and the ways in which territories are opened up for solar development can promote socio-technical transformation, but equally reproduce business-as-usual geographical and geopolitical power constellations (Avila et al 2022).…”
Section: Review and Methodology: Towards Identifying Principles Of So...mentioning
confidence: 99%
“…The global imperative to implement large-scale solar infrastructures to swiftly mitigate the climate crisis has led to a 'global land rush' (Scheidel and Sorman 2012), often exacerbating land-use conflicts by 'green grabbing' productive spaces for marginalised producers (Avila et al 2022;EJAtlas 2019;Franco and Borras 2019). Acquiring space for utility-scale solar projects has often entailed the dispossession of land from marginalised farmers (Bedi 2019;Stock and Birkenholtz 2021;Yenneti, Day and Golubchikov 2016).…”
Section: The Need For Solidaric Solar Energy Geographiesmentioning
confidence: 99%
“…The work of radical urban geographer William Bunge challenging the inequality and exploitation in Detroit exemplifies a longstanding concern in geography with the direct experiential knowledge in research and the social responsibility of academic researchers (Bunge, 2011). Bunge's legacy of urban expedition in Detroit has been continued while not that prevalent yet in urban poverty and counter-mapping study of developed and developing countries (Yapa, 2009;Avila et al, 2021).…”
Section: Place-based Community Engagement and Geographymentioning
confidence: 99%
“…Environmental justice is a widely acknowledged field in the community mapping both in developed and developing countries (Haklay and Francis, 2018;Avila et al, 2021). Environmental justice discourse has diverse themes and issues, and many of its everyday (Sieber, 2006;Kyem, 2021).…”
Section: Social Relevance and Environmental Issues As An Examplementioning
confidence: 99%
“…Although renewable technologies infrastructure still requires fossil fuels, life cycle greenhouse gas emissions are significantly lower for technologies powered by renewable resources than those powered by non-renewable ones [10]. Renewable energy corporations have been criticized for perpetuating social injustices [11] or using vast land extensions for energy production. However, when comparing normalized land use for both renewable and conventional energy sources, it has been found that some types of renewables, like PV, actually use the least amount of land [12].…”
Section: Introductionmentioning
confidence: 99%